2016
DOI: 10.1016/j.ijnurstu.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

The daily relationships between staffing, safety perceptions and personality in hospital nursing: A longitudinal on-line diary study

Abstract: BackgroundThe association between poor staffing conditions and negative patient safety

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 57 publications
0
29
0
1
Order By: Relevance
“…Fuller details of the study method including more information pertaining to participants, design, procedure and analysis have been published previously [53].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuller details of the study method including more information pertaining to participants, design, procedure and analysis have been published previously [53].…”
Section: Methodsmentioning
confidence: 99%
“…To assess whether nurses perceived they were able to practise safety, referred to as safe practitioner measure [53], taking the conditions on shift into account-participants were asked to respond to one statement on a 5-point scale (ranging from 1 = strongly disagree to 5 = strongly agree). A higher score on this outcome represented a more favourable perception.…”
Section: End Of Shift Daily Measuresmentioning
confidence: 99%
“…In line with previous research, the two burnout facets of Emotional Exhaustion and Depersonalisation were included (Halbesleben et al, 2008). Safety perceptions were used to measure patient safety, as previous research has suggested these are associated with objectively measured patient safety outcomes (Hansen et al, 2011, Hofmann and Mark, 2006, Mardon et al, 2010 and are useful for detecting variations in perceived safety between individual practitioners (Halbesleben et al, 2008, Louch et al, 2016. There were two hypotheses: Hypothesis 1: There will be a direct association between depressive symptoms and patient safety perceptions.…”
Section: The Study Aimsmentioning
confidence: 99%
“…Perceptions were reported at both the individual level and the work area/unit level, based on evidence that these measures provide useful and complementary information that vary between nurses in response to stress and individual differences (Louch et al, 2016).…”
Section: Patient Safety Perceptionsmentioning
confidence: 99%
See 1 more Smart Citation